Persepsi dan Ketertarikan Siswa SMA Terhadap Profesi Petani (Studi Kasus : SMA N 3 Jember) - Rosa, Firlana; Prayuginingsih, Henik; Fauzi, Nurul Fathiyah (Universitas Galuh, 2025)
In recent years, the agricultural sector has experienced the Aging Farmer phenomenon in almost all over the world, both developed and developing countries. The Aging Farmer phenomenon is a condition where the number of young farmers is less than the number of old farmers. This study aims to analyze: (1) the perception of SMAN 3 Jember students towards the profession of farmer; (2) the interest of SMAN 3 Jember students towards the profession of farmer.; (3) the relationship between the perception of SMAN 3 Jember students and their interest in the profession of farmer; (4) efforts to reduce the Aging Farmer phenomenon in SMAN 3 Jember students. The study used primary and secondary data with a sample size of 51 male students and 27 female students in grade XII. Data were analyzed using the Likert Scale, Descriptive Analysis and Spearman Rank Correlation. The results of the study showed that: (1) SM N 3 Jember students have a good perception of the profession of farmer with an average score of 72.19%; (2) the interest of SMAN 3 Jember students towards the profession of farmer is categorized as good with an average score of 71.54%; (3) There is a strong and significant relationship between perception and students' interest in the farming profession (rs= 0.702); (4) one of the efforts to reduce the aging of farmers in the SMAN 3 student environment is the existence of farmer income that guarantees life as answered by 35.90% of students.